CAPACITY DEVELOPMENT, GOVERNANCE, AND SUSTAINABLE DEVELOPMENT IN SOUTH SUDAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This study aimed at establishing the impact of Capacity development, Governance and Sustainable development in South Sudan with a particular reference of UNHCR and UNDP in South Sudan. The objectives of the study were to; examine the relationship between Capacity development and Sustainable development, examine the relationship Governance and Sustainable development and to analyse the factor structure of Capacity development and Governance on Sustainable development.The study employed a cross sectional and descriptive design while using qualitative and quantitative approaches. The study population was 48,689, selected using purposive and simple random sampling technique. The sample size determination was made using Krejcie and Morgan Table (1970) formula. The sample size was 280. The data analysis was made using Statistical package for social scientists (SPSS 20). The major findings of the study were that there was a positive relationship between; capacity development and sustainable development in the South Sudan (r = 0.701, P-value < 0.01), Governance and Sustainable development (r = 0.680, P-value < 0.01) and lastly variables explained (R= 0.654) a combination of Capacity development and Governance in assessing the level to which they can predict the level of Sustainable development in the Country like South Sudan.